Polymorphism in Languria taedata LeConte, its occurrence in coastal Louisiana Spartina marshes, and clarification of some Motschulsky languriine types (Coleoptera: Erotylidae: Languriinae) - Gimmel, Matthew L.; Carlton, Christopher E.; White, William H. (Zootaxa, 2012)
We clarify the diagnosis and geographic distribution of the widespread, variable eastern coastal species Languria taedataLeConte, 1854, in North America. After examining types and the range of variation and geographical distribution of thespecies, we propose synonymy of L. erythrocephalus Blatchley, 1924, with L. taedata, new synonymy. We report the dis-covery of an all-piceous form (“Form C”), the first of the genus, found primarily along the western Gulf Coast of the Unit-ed States. The recognition of this form requires a modification to the most recent key to North American genera ofLanguriinae. The larvae of L. taedata feed within the stems of Spartina alterniflora Loisel (Poaceae). We provide addi-tional notes on the occurrence of L. taedata in coastal marshes in Louisiana. The types of L. apicalis Motschulsky, L. ni-griceps Motschulsky, L. obscura Motschulsky, and L. rufiventris are reexamined. A revised synonymic checklist is provided for North American Languriini.